Retreatment Saluran Akar pada Gigi Anterior Rahang Atas dengan Follow Up Mahkota Komposit Indirek - Irfan Fathon; Jeffrey Jeffrey (e-GiGi, 2023)
Abstract: Endodontic treatment aims to eliminate infection, pain, and maintain teeth in the oral cavity. This case report discussed the indication, risks, and case management of root canal retreatment of tooth 61 in a five-year-old patient at the Dental and Oral Teaching Hospital, Cimahi, Indonesia. We reported a five-year-old girl with complaint of a large cavity in her upper anterior tooth since a year ago. She had a root canal treatment but the filling fell out. The treatment was root canal retreatment of maxillary anterior teeth followed by an indirect composite crown replacement. After completion of the treatment, there were no complaints in tooth 61 and the indirect composite crown had well adapted. In this case, retreatment was needed to prevent the risk of infection and pain due to marginal leakage that could occur due to the release of the restoration. Therefore, it was expected that due to pulpal treatment, the primary teeth could be maintained in their position. This aimed to prevent growth and development disorders of the jaw arch, so, it could function properly. In conclusion, retreatment of the root canal in this case aimed to prevent the occurrence of infection caused by the release of restoration on the tooth that had previous endodontic treatment. The ultimate goal of retaining the primary teeth in the oral cavity was to maintain the jaw arch’s esthetics and masticatory function. Keywords: retreatment; root canal; aesthetics; mastication   Abstrak: Perawatan endodontik bertujuan untuk mengeliminasi infeksi, rasa nyeri, dan memper-tahankan gigi dalam ronga mulut. Laporan kasus ini membahas mengenai indikasi, risiko, dan penatalaksanaan kasus dari retreatment saluran akar gigi 61 pada pasien anak di Rumah Sakit Gigi dan Mulut Pendidikan (RSGMP). Kasus seorang anak perempuan, 5 tahun dengan keluhan gigi depan atas berlubang besar sejak 1 tahun lalu, pernah dilakukan perawatan saluran akar namun tambalannya terlepas. Perawatan yang dilakukan ialah retreatment saluran akar pada gigi anterior rahang atas dengan follow up mahkota komposit indirek. Setelah selesai dilakukan perawatan, tidak ada keluhan pada gigi 61 dan mahkota komposit indirek telah beradaptasi dengan baik. Retreatment diperlukan pada kasus ini dengan tujuan untuk mencegah terjadinya risiko infeksi dan nyeri akibat kebocoran marginal yang dapat terjadi akibat terlepasnya restorasi. Dengan perawatan pulpa gigi sulung, gigi dapat dipertahankan pada posisinya. Hal ini bertujuan agar tidak terjadi gangguan tumbuh kembang pada lengkung rahang dan dapat berfungsi sebagaimana mestinya. Simpulan kasus ini ialah retreatment saluran akar bertujuan untuk mencegah terjadinya infeksi akibat terlepasnya restorasi pada gigi yang telah dilakukan perawatan endodontik sebelumnya, dengan tujuan akhir mempertahankan gigi sulung di rongga mulut untuk menjaga lengkung rahang, estetika, dan fungsi mastikasi. Kata kunci: retreatment; saluran akar; estetik; mastikasi